2014
DOI: 10.1016/j.celrep.2014.10.057
|View full text |Cite
|
Sign up to set email alerts
|

3D Clustering of GABAergic Neurons Enhances Inhibitory Actions on Excitatory Neurons in the Mouse Visual Cortex

Abstract: Neocortical neurons with similar functional properties assemble into spatially coherent circuits, but it remains unclear how inhibitory interneurons are organized. We applied in vivo two-photon functional Ca(2+) imaging and whole-cell recording of synaptic currents to record visual responses of cortical neurons and analyzed their spatial arrangements. GABAergic interneurons were clustered in the 3D space of the mouse visual cortex, and excitatory neurons located within the clusters (insiders) had a lower ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…Consistent with the nonrandom connectivity in L2/3, but counter to areal uniformity (Kim et al, 2017), we have found that PV somata and terminals in L1-2 are spatially clustered (Ichinhoe et al 2003;Maruoka et al, 2017;Znamenskiy et al, 2018). Similar to the spatial clustering of IPSC amplitude (Ebina et al, 2014) and consistent with clustering of visual response properties and strong inhibition between visually co-tuned PVs and PNs (Ji et al, 2015;Znamenskiy et al, 2018) the results show stronger local inhibition in interpatches than in patches. This may be due to larger, more proximal and/or the higher density of PV synapses onto PNs (Kubota et al, 2015;Stüber et al, 2015).…”
Section: Subnetwork-selective Targeting Of Pns and Pvssupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with the nonrandom connectivity in L2/3, but counter to areal uniformity (Kim et al, 2017), we have found that PV somata and terminals in L1-2 are spatially clustered (Ichinhoe et al 2003;Maruoka et al, 2017;Znamenskiy et al, 2018). Similar to the spatial clustering of IPSC amplitude (Ebina et al, 2014) and consistent with clustering of visual response properties and strong inhibition between visually co-tuned PVs and PNs (Ji et al, 2015;Znamenskiy et al, 2018) the results show stronger local inhibition in interpatches than in patches. This may be due to larger, more proximal and/or the higher density of PV synapses onto PNs (Kubota et al, 2015;Stüber et al, 2015).…”
Section: Subnetwork-selective Targeting Of Pns and Pvssupporting
confidence: 81%
“…GABAergic neurons in L2/3 of mouse V1 are clustered in the tangential plane and are radially aligned in L5 with subcortically projecting PNs (Ebina et al, 2014. Maruoka et al, 2017.…”
Section: Clustering Of Gabaergic Neurons It Has Been Reported That Pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SLS can achieve higher frame rates and it is characterized by an inherently higher ratio between the cellular dwell time and total frame time than imaging with resonant mirrors. For this reason, SLS may be particularly useful in the presence of sparse cellular labeling such that observed in some transgenic animal models expressing GECIs Song et al, 2017) and when imaging specific classes of interneurons (Ebina et al, 2014;Kato et al, 2013) or small astrocyte structures displaying fast calcium kinetics (Bindocci et al, 2017;Stobart et al, 2018). Future developments of SLS may include 3D SLS using electrically tunable lenses (Grewe et al, 2011), two-color SLS, and SLS of functional indicators combined with holographic optogenetic stimulation (Bovetti and Fellin, 2015;Forli et al, 2018;Mardinly et al, 2018;Packer et al, 2015;Papagiakoumou et al, 2010;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these anatomical differences between mice and higher species, one notable functional difference that has been found is the percentage of responsive neurons in the cortex. Studies have consistently reported that around half of the neurons in mouse V1 respond significantly to grating stimuli (Ebina et al, 2014;Kerlin et al, 2010;Bonin et al, 2011;Mrsic-Flogel et al, 2007;Sohya et al, 2007;Smith and Häusser, 2010;Ayzenshtat et al, 2016;Palagina et al, 2017). However, the few studies done in V1 in primates and cats indicate a much higher percentage of responsive neurons to grating stimuli -typically more than 90% of the cells are responding (Nauhaus et al, 2012;Ikezoe et al, 2013;Kara and Boyd, 2009).…”
Section: Introductionmentioning
confidence: 99%